Regional Training on Sub-Seasonal Prediction for Eastern and Southern Africa - Ambaw, Gebermedihin; Bekele, Tamirat; Amha, Yosef; Seid, Hussen; Gudoshaa, Masilin; Koech, Eunice; Demissie, Teferi; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
Eastern and Southern African countries face increasing vulnerability to extreme climate events, including droughts, floods, and cyclones, which have intensified in recent years. These events severely disrupt livelihoods, infrastructure, and recovery efforts, as seen during the 2020–2022 East Africa drought, the 2023 floods, and Cyclone Freddy’s impacts in Southern Africa. Such persistent climate extremes highlight the urgent need for improved disaster preparedness, resilience-building measures, and adaptive capacities in the region. The Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA) project addresses these challenges by advancing climate information services and promoting climate-smart agricultural technologies. In collaboration with the International Livestock Research Institute (ILRI), ICPAC organized a regional training program on sub-seasonal forecasting using the Python-based Climate Predictability Tool (PyCPT v2.8). This advanced tool bridges the forecasting gap between short-term weather and seasonal predictions, offering critical insights for agriculture, water management, energy, and disaster preparedness. The training aimed to strengthen the capacity of National Meteorological and Hydrological Services (NMHSs) and ICPAC staff in sub-seasonal operational forecasting. By equipping stakeholders with enhanced forecasting tools and skills, the initiative seeks to improve decision-making, mitigate the impacts of extreme weather events, and safeguard the livelihoods of vulnerable communities across the region. A total of 35 participants (26% female) from 15 countries actively engaged in this training, reflecting its broad regional impact and collaborative approach.